Can the Special Economic Zones Promote the Green Technology Innovation of Enterprises? An Evidence From China - Liu, Xiao; Zhang, Jun; Liu, Tinghua; Zhang, Xiangjian (Frontiers in Environmental Science, 2022)
Addressing to global climate change is the responsibility of all mankind, and original green technology innovation is the key to achieving the goal of "carbon neutrality". Under the target of "carbon neutrality", Whether China's special economic zones can promote the green technology innovation of enterprises, which is very important for achieving green and high-quality development. This study examines the impact of special economic zones (SEZs) programs on enterprises’ green technology innovation by constructing a quasi-natural experiment using data of Chinese listed companies (collected from 2000 to 2017), and green patent applications. The empirical results showed that the SEZ program significantly promoted the green technology innovation of enterprises. The number of green patent applications of enterprises in zones has increased by 17.02%. The promotion effect was more significant on enterprises in provincial development zones, central state-owned, and in the central and eastern regions. In the short term, the green innovation promotion effect is mainly derived from the effect of preferential policy subsidies. While in the long run, the role of the agglomeration effect gradually emerged. This study provides empirical evidence for green and high-quality development. And also this study provides a new policy reference for achieving a win-win situation between industrial agglomeration and ecological environment